2021
DOI: 10.1097/gme.0000000000001806
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and cancer risk in women in later life: a systematic review and meta-analysis of cohort studies

Abstract: Importance: Results of this work may provide some guidance for subsequent ovarian cancer screening in women with preeclampsia and provide new directions for future studies. Objective: This study investigated the difference in cancer risk between women with preeclampsia and women with a normal pregnancy. Evidence Review: Electronic databases, namely PubMed, Embase, and the Cochrane Library, were searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…For cognitive outcomes, it remains uncertain if there is a difference between early-onset and late-onset pre-eclampsia 302 . An effect of pre-eclampsia on malignancies has recently been identified 307 .…”
Section: Long-term Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For cognitive outcomes, it remains uncertain if there is a difference between early-onset and late-onset pre-eclampsia 302 . An effect of pre-eclampsia on malignancies has recently been identified 307 .…”
Section: Long-term Health Outcomesmentioning
confidence: 99%
“…In a meta-analysis of >5 million women, a history of pre-eclampsia was associated with a lower risk of breast cancer (RR 0.88, 95% CI 0.83-0.93) and increased risk of ovarian cancer (RR 1.82, 95% CI 1.16-2.85) 307 .…”
Section: Long-term Health Outcomesmentioning
confidence: 99%
“…A population study also demonstrated no association between antiangiogenic factor levels during pregnancy and risk of breast cancer in the first decade after delivery (27). However, in a recently published meta-analysis that included 13 cohort studies comprising 5,254,150 participants, women with preeclampsia had a lower incidence of breast cancer than women without preeclampsia (28). One possible mechanism for this reduced risk of breast cancer is hormonal changes and responsiveness to hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Certain pregnancy complications also may be associated with subsequent maternal breast cancer risk, for example preeclampsia, but because these conditions are rare, the investigations require large studies like the Nordic Project to reach the statistical precision required for accuracy. Several studies have shown a reduced risk of breast cancer among women with a history of preeclampsia, a hypertensive disorder of pregnancy, compared with those with normotensive pregnancies (17). Interestingly, one study demonstrated a marked reduction with elevated mean arterial pressure (MAP) (18) and with systolic blood pressure increasing from mid-to late pregnancy below the diagnostic criterion for hypertension (i.e., in normotensive pregnancies) (19).…”
Section: Breast Cancermentioning
confidence: 99%